Evaluation of Toxicity and Anti-Breast Cancer Potential of Methanolic Leaf Extract of Anastatica hierochuntica in DMBA Induced Rat Model - Rameshbabu, Saranya; Messaoudi, Safia A.; Alsaleh, Abrar B.; Cordero, Mary Anne Wong; Ganesh, Kavitha; Rashid, Najwa Abdur; Saadani, Raja El Hasnaoui-; Yacoob, Syed Ali Mohamed (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Anastatica hierochuntica has been traditionally used in herbal medicine for its therapeutic effects, but its safety and efficacy have not been comprehensively assessed. This study investigated the Methanolic Leaf (ML) extracts of A. hierochuntica acute and sub-acute toxicity in Sprague-Dawley rats and its anti-breast cancer potential in a 7,12-Dimethylbenz[a]Anthracene (DMBA)-induced rat model. Materials and Methods: Acute and sub-acute oral toxicity studies were conducted following the Organization for Economic Co-operation and Development (OECD) guidelines 423 and 407, respectively. Hematological and biochemical parameters were analyzed in blood and serum respectively. Breast tissues were examined for oxidative stress including Lipid Peroxidation (LPO), Catalase (CAT), and Reduced Glutathione (GSH). Histopathological assessments were performed on liver, kidney, spleen, and mammary tissues. The anti-breast cancer study involved DMBA-induced rats treated with ML (200 and 400 mg/ kg) or tamoxifen. Results: The acute toxicity study indicated no treatment-related mortality or significant physiological changes at doses up to 2000 mg/kg. Sub-acute toxicity assessment revealed no adverse effects up to 1000 mg/kg. suggest that ML extract has a high safety profile, with a No-Observed-Adverse-Effect Level (NOAEL) above 1000 mg/kg. In the DMBA-induced model, ML treatment significantly (p<0.05) reduced tumor incidence and tumor weight, with the 400 mg/kg dose showing the greatest efficacy. ML also improved oxidative stress markers by decreasing LPO levels and increasing CAT and GSH activity. Histopathological analysis revealed a reduced tumour burden and improved mammary architecture in ML-treated groups compared to untreated controls. Conclusion: The ML extract of A. hierochuntica demonstrated significant anti-breast cancer potential in DMBA-induced rats, alongside a favourable toxicity profile warranting further investigation for potential therapeutic applications.
Keywords: Acute and sub-acute toxicity; DMBA; Anti-breast cancer; Anastatica hierochuntica